2014
DOI: 10.1038/nature13577
|View full text |Cite
|
Sign up to set email alerts
|

The alarmin IL-33 promotes regulatory T-cell function in the intestine

Abstract: Foxp3+ regulatory T cells are abundant in the intestine where they prevent dysregulated inflammatory responses to self and environmental stimuli. It is now appreciated that Treg cells acquire tissue-specific adaptations that facilitate their survival and function1; however, key host factors controlling the Treg response in the intestine are poorly understood. IL-1 family member IL-33 is constitutively expressed in epithelial cells at barrier sites2 where it functions as an endogenous danger signal or alarmin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

68
957
7
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 870 publications
(1,038 citation statements)
references
References 35 publications
68
957
7
6
Order By: Relevance
“…effector macrophages by sialylated Fc critically depends on production and secretion of IL-33 (29). Recent findings have indicated that IL-33 has a positive effect on T reg -cell stimulation and activation (31,32) and thereby contributes to the suppression of inflammation in a mouse model of experimental colitis (33). To test the possibility that sFc-induced production of IL-33 may also contribute to T reg -cell stimulation, we confirmed that naïve CD4 + T cells isolated from C57BL/6 wild-type mice, cultured for 3 d in the presence of anti-CD3 and anti-CD28 antibodies and TGF-β to specifically drive T reg -cell differentiation and then treated with IL-33, had a synergistic effect on T reg -cell differentiation as well as on Foxp3 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…effector macrophages by sialylated Fc critically depends on production and secretion of IL-33 (29). Recent findings have indicated that IL-33 has a positive effect on T reg -cell stimulation and activation (31,32) and thereby contributes to the suppression of inflammation in a mouse model of experimental colitis (33). To test the possibility that sFc-induced production of IL-33 may also contribute to T reg -cell stimulation, we confirmed that naïve CD4 + T cells isolated from C57BL/6 wild-type mice, cultured for 3 d in the presence of anti-CD3 and anti-CD28 antibodies and TGF-β to specifically drive T reg -cell differentiation and then treated with IL-33, had a synergistic effect on T reg -cell differentiation as well as on Foxp3 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the relative dearth of Treg cells was absent in the NZW BM. Several groups have described distinct Treg subpopulations in the colonic lamina propria (LP), which differ in their origin, relation to the gut microbiota, and expression of key transcription factors (23,(32)(33)(34)(35). Treg cells were found in low proportions in the NZW colonic LP (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cytokines-IL-2 foremost-are thought to be the main controllers of Treg proportions and numbers (15)(16)(17)(18)(19)(20)(21)(22), although the relative importance of these controllers varies with location and subphenotype [e.g., the alarmin IL-33 has a more profound role in tissue Tregs (21)(22)(23)]. Perhaps surprisingly, in light of this apparently tight control, there is a wide range of variation in Treg proportions, with several studies having observed up to fourfold variation in the blood of healthy humans (e.g., refs.…”
mentioning
confidence: 99%
“…31 The "alarmin" IL-33/ST2 axis has recently been delineated to play a key role in the loss of epithelial integrity caused by microbial translocation of the mucosal barrier in mice and humans. [32][33][34][35] Despite this relevant axis, an impact of the microbiota remains a less well established and controversial risk factor for aGVHD pathogenesis. 36,37 In conclusion, this study highlights the potentially detrimental role of ATB in aGVHD severity and in OS.…”
Section: Discussionmentioning
confidence: 99%